Students’ Mathematical Connection Error in Solving PISA Circle Problem - Hidayati, Vivi Rachmatul; Subanji, Subanji; Sisworo, Sisworo (Universitas PGRI Madiun, 2020)
The mathematical connection is one of the competencies in NCTM that students need to have. Mathematical connections can help students understand material and mathematical concepts easily. In addition, mathematical connections can help students in solving mathematical problems. Even so, mathematical connection errors are still made by some students. Mathematical connection errors made by students when solving geometry problems, especially about a circle. The purpose of this study is to describe the mathematical connection errors made by students in solving problems adapted from PISA problems focusing on circle material. This research method is descriptive-qualitative. Prospective subjects are 20 of 8th-grade students in one of the junior high schools in Malang who have studied about a circle. Based on the distribution of answers, two subjects were selected in this study. After going through the interview process, the data obtained in the form of work results and interview transcripts. Based on the results of research, mathematical connection errors made by research subjects in the form of not being able to use mathematics in mathematical problems; can't find connections between topics in mathematics; unable to understand the representation of concepts in mathematical problems, and draw relationships between procedures on mathematical problems